2021
DOI: 10.33774/coe-2021-l88qk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Speech Perception through Face Masks by Children and Adults

Abstract: Face masks can cause speech processing difficulties. However, it is unclear to what extent these difficulties are caused by the visual obstruction of the speaker’s mouth or by changes of the acoustic signal, and whether the effects can be found regardless of semantic context. In the present study, children and adults performed a cued shadowing task online, repeating the last word of English sentences. Target words were embedded in sentence-final position and manipulated visually, acoustically, and by semantic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…An additional limitation of the current study is that participants were all adults. Recent work (Schwarz et al, 2021) has shown that children also exhibit differences in the way they perceive face-masked speech-and might also make different clear speech adaptations to overcome the mask. Furthermore, the study included only one type of face mask, a fabric face-mask.…”
Section: Discussionmentioning
confidence: 99%
“…An additional limitation of the current study is that participants were all adults. Recent work (Schwarz et al, 2021) has shown that children also exhibit differences in the way they perceive face-masked speech-and might also make different clear speech adaptations to overcome the mask. Furthermore, the study included only one type of face mask, a fabric face-mask.…”
Section: Discussionmentioning
confidence: 99%